ZnO Coated Anodic 1D TiO2 Nanotube Layers: Efficient Photo-Electrochemical and Gas Sensing Heterojunction. - Kuberský, Petr; Ng, Siowwoon; Krbal, Milos; Přikryl, Jan; Gärtnerová, Viera; Moravcová, Daniela; Sopha, Hanna; Zazpe, Raul; Yam, Fong Kwom; Jäger, Aleš; Hromádko, Luděk; Beneš, Ludvík; et al. (Wiley, 2017)
We demonstrate in this work a fascinating synergism of a high surface area heterojunction between TiO2 in the form of ordered 1D anodic nanotube layers of a high aspect ratio and ZnO coatings of different thicknesses, produced by atomic layer deposition. The ZnO coatings effectively passivate the defects within the TiO2 nanotube walls and significantly improve their charge carrier separation. Upon the ultraviolet and visible light irradiation, an increase of the ZnO coating thickness from 0.19 to 19 nm and an increase of the external potential from 0.4 - 2 V, yields up to 8-fold enhancement of the photocurrent density. This enhancement translates into extremely high incident photon to current conversion efficiency of ~95 %, which is among the highest values reported in the literature for TiO2 based nanostructures. In addition, the photoactive region is expanded to a broader range close to the visible spectral region, compared to the uncoated nanotube layers. Synergistic effect arising from ZnO coated TiO2 nanotube layers also yields an improved ethanol sensing response, almost 11-fold compared to the uncoated nanotube layers. The design of the high-area 1D heterojunction presented here opens pathways for the light- and gas-assisted applications in photocatalysis, water splitting, sensors, and so on.
Keywords: self-organized TiO2 nanotubes; ZnO coatings; ALD; charge separation; ethanol sensing